Polyclonal B cells acquire LCMV antigens in a GP1-dependent manner. - Gabriel Chamberlain; Guillaume L Lopez; Léa Bourguignon; Xavier Laulhé; Yasmine Adda-Bouchard; Tania Charpentier; Rebekah Honce; Jason W Botten; Alain Lamarre (PLoS Pathogens)
The polyclonal, T-dependent nature of hypergammaglobulinemia during murine infection with LCMV is well defined, however the mechanism by which polyclonal B cells acquire antigens for presentation remains unknown. Here we use LCMV-specific CD4 + transgenic T cells to explore several hypotheses for B cell antigen uptake. We found that antigens produced by cells infected with LCMV in vitro are available to polyclonal B cells and their presentation to CD4+ T cells enabled robust co-activation. The in vitro nature of our model demonstrates that in vivo factors such as cytokine milieu and antigen release by NK/CD8+ are not required. We show that non-replicative UVC-irradiated LCMV enables antigen access to B cells, thus productive infection of B cells is not required for antigen acquisition. B cells loaded with LCMV antigens in vitro can efficiently present these antigens to CD4+ T cells in LCMV-infected mice, thereby validating our model in vivo. Using transmission electron microscopy we identified LCMV-GP bearing particles of various sizes including <50nm, a size accessible to B cells via pinocytosis. The particles morphologically resemble exosomes or viral particles (infective or defective interfering). We show that polyclonal B cell access to Ag is maintained when exosome release or viral defective interfering particle release is inhibited. Finally, we used a monovalent Fab derived from the LCMV-neutralizing antibody KL25 to show that access to the viral GP1 protein is important in order for polyclonal B cells to efficiently acquire LCMV antigen for presentation, suggesting the presence of a GP1 receptor on B cells.